Simple sensitivity calculation for inverse design problems in electrical engineering. Issue 3 (2014) - ,
Abstract : Purpose – The purpose of this paper is to present a simple approach for calculation of the sensitivities in the free‐form inverse design problems. The approach is based on the analogy with the similar tasks used in the signal‐processing analysis. In the proposed case it is not required to solve an adjoint problem as in the most of the similar optimization tasks. The simulation engine used in the background is a Fast Boundary Element Method. The approach is validated on some known benchmark problems.Design/methodology/approach – Inverse design is recognized nowadays as a crucial scientific grand challenge. Contrary to the conventional approach ("Given the structure, find the properties") it purses a new paradigm ("Given the desired property, find the structure"). Inverse class of problems has a broad application area, from the material‐, medical‐, bio‐ to the engineering‐class of problems. When dealing with the inverse design in free‐form optimization of the engineering problems the typical approach is to calculate the adjoint problem. Calculation of the adjoint problem mostly requires the costly calculation of the gradients, which makes the whole optimization procedure rather expensive due to the high computational burden required for their solution.Findings – In this paper it is proposed a novel Simple Sensitivity Approach to get in a fast way the response (sensitivity) function of the analyzed structure. The simulation engine used in the background is the Fast Boundary Element Method.Originality/value – Novel approach for inverse design when performing the free‐form optimization of engineering problems.